Identifying, measuring and management risks in Russian secondary stock markets - Elena Lapsina; Eric Thor; Roman Melnikov (European Regional Science Association (ERSA), 1998)
: This paper outlines the changes and challenges of Emerging Russian Stock Market and investment strategy of portfolio management for the period 1996-1998 . It also taste the West models of optimization of portfolio risks and investment decisions for Russia. The major purpose of this article was to enhance the understanding of the participants in securities markets and enhance the performance of its stock and Emerging securities. This article will review the trends in the markets and help focus on the corporate risks and management and a detailed and developed conception of the mechanism of the initial public offerings and public placement of securities the global stock markets such as the U.S., Western Europe and emerging markets. It also outlined the regulatory structure and investor?s risk management tools required by western investors. In light of the recent ?financial crisis? in Russia and other major markets such as Asia, these tools will be increasing important. During much of the past decade the Russian Securities market has been developing into a number of areas including federal securities (GKO-OFZ), sub-federal (oblast) and municipal issues, corporate securities, Ag Bonds, futures, forward contracts and currency instruments. This article is developing in all those areasm .These will be increasing important in light of the new banking environment and securities laws and regulations. In 1997 Russia has joined the league of the few emerging markets that have market capitalizations of over 100 Billion. As of June 30, 1997 the capitalization is 104 Billion and has a YTD of 134 %. The recent ?Asian induced? corrections in the markets have reduced this by 20-40% according to private estimates. Nevertheless, it remains one of the most vibrant emerging securities markets in the world. The training focused on a number of issues related to emerging market securities including privatization, auctions, IPO?s and new products in the securities markets.
Keywords: 330